CXCR4, the master regulator of neutrophil trafficking in homeostasis and disease. (23rd May 2018) - De Filippo, Katia; Rankin, Sara M.
Abstract: Background: Chemokines play a critical role in orchestrating the distribution and trafficking of neutrophils in homeostasis and disease. Results: The CXCR4/CXCL12 chemokine axis has been identified as a central regulator of these processes. Conclusion: In this review, we focus on the role of CXCR4/CXCL12 chemokine axis in regulating neutrophil release from the bone marrow and the trafficking of senescent neutrophils back to the bone marrow for clearance under homeostasis and disease. We also discuss the role of CXCR4 in fine‐tuning neutrophil responses in the context of inflammation.